2012
DOI: 10.1007/978-3-642-29011-4_20
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Simulating Features of Composite Order Bilinear Groups in the Prime Order Setting

Abstract: In this paper, we explore a general methodology for converting composite order pairingbased cryptosystems into the prime order setting. We employ the dual pairing vector space approach initiated by Okamoto and Takashima and formulate versatile tools in this framework that can be used to translate composite order schemes for which the prior techniques of Freeman were insufficient. Our techniques are typically applicable for composite order schemes relying on the canceling property and proven secure from variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
206
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(217 citation statements)
references
References 43 publications
1
206
0
Order By: Relevance
“…As in [10], we use dual pairing vector space to achieve the canceling and parameter hiding properties in the prime order setting.…”
Section: Complexity Assumptionsmentioning
confidence: 99%
See 4 more Smart Citations
“…As in [10], we use dual pairing vector space to achieve the canceling and parameter hiding properties in the prime order setting.…”
Section: Complexity Assumptionsmentioning
confidence: 99%
“…In 2010, Freeman [8] provided a generic method for transforming schemes in composite order settings [4,9,11] to prime order settings, but the method can not be applied to some schemes. Lewko [10] observed that the method of [8] perfectly simulated the "canceling" property, yet was not a useful approach to achieve the "parameter hiding" property. Lewko [10] used dual pairing vector space which was proposed by Okamoto and Takashima [13,14] to simulate both properties in the prime order setting, and got a fully secure IBE scheme akin to the one in [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations